Rancang Bangun Sistem Informasi Koperasi Guru Dengan Metode Flat Berbasis Web - Fahimah, Nurul; Putri, Raissa Amanda (Journal of Information System Research (JOSH), 2024)
The design carried out in this research is a website-based teacher cooperative information system at SD PAB 23 using the flat method. This research was carried out in stages using the waterfall method which is used as a system development method to create a website. The stages carried out include system validation and testing, this is the basis for proving whether the waterfall method has been successfully used in creating a teacher cooperative information system website to make it easier for existing cooperative members, with the flat method which is the basis for calculating rates. Interest on the teacher cooperative information system website can run well. This website aims to make it easier for admins to analyze data on savings, loans and payments which can be viewed easily and calculated automatically. This is a benefit for all cooperative members who join, the information system also helps us in managing data so that it is more systematic and neat in processing existing data. This cooperative was started in 2013 as a means to facilitate the material needs of all teachers at the school. This has been approved by all members of the cooperative, totaling 27 members at this time, to the extent that the applicable interest is used using the flat method, which is done by calculating the total interest based on the amount of the loan made, so as to produce the borrower's payment amount each month.